STUDENTS’ EMOTIONAL RESPONSES TOWARD TEACHER’S DIRECT WRITTEN CORRECTIVE FEEDBACK - Cindy Fatika Sari; Maman Suryaman; Elih Sutisna Yanto (STKIP Siliwangi, 2022)
This study aims to find out what emotional responses students after receiving to Direct Written Corrective Feedback (DWCF) from the teacher in their writing assignments. The research design used in this research is a narrative case study design. The respondents of this study were the students of Senior high school in Karawang. To collect students’ emotional response data, semi-structured interviews and students' reflective journals are used. Then, collected data were analyzed by using thematic analysis. The results revealed that students’ emotional responses toward teacher’s direct written corrective feedback include positive and negative responses. The positive responses were happy (6), satisfaction (5), motivated (3). While, negative responses were surprised (1), disappointed (2), dissatisfaction (1). Based on these findings, it can be concluded that most of students responded the teacher’s feedback positively. The reason why most of students gave the positive responses was revealed by the result of interview that students feel happy because the feedback that the teacher provides is very useful.